The effects of (within and with EU) regional integration: Impact on real effective exchange rate volatility, institutional quality and growth for MENA countries - Leonardo Becchetti; Iftekhar Hasan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
We analyse two potential effects arising from regional (and with EU) integration—increased quality of institutions (including the quality of financial institutions) and, economic policies and reduced multilateral exchange rate volatility—in a conditional convergence growth framework for MENA countries. To this purpose we outline an ad hoc methodology which implements the traditional bilateral exchange rate measures to test effects of multilateral exchange rate volatility on growth of per capita GDP. Our estimates show that both factors (quality of institutions and reduction of multilateral volatility) significantly and positively affect growth and conditional convergence. We observe that MENA countries are not far from EU and OECD countries in terms of exchange rate volatility, but much below in terms of institutional quality. We finally simulate the potential effects of an improvement in institutional quality in MENA countries on their process of growth and conditional convergence. We conclude arguing that regional integration may be highly beneficial for such countries, mainly because of its effects on institutional quality. – institutions ; exchange rate ; economic policy
Keywords: F31; F36; 330; Handelsregionalismus; Wechselkurs; Volatilität; EU-Staaten; OECD-Staaten; MENA-Staaten